Physiological and behavioural responses to thermal stresses in tennis - Morante, S. (Medicine and Science in Tennis, 2008)
The aim of this thesis was to obtain comprehensive data on environmental and metabolic heat stress, and body temperature regulation during competitive singles tennis matches over each of the seasons in Sydney, Australia. These data were then be used to determine whether a steady-state core body temperature and thermal comfort are being achieved in tennis, in ad di tion to the mechanisms responsible for their attainment (i.e. autonomic / physiological thermoregulation or behavioural / psychological thermoregulation?). These data were also used for the rational analysis of heat stress, which will enable pre di ction of all thermal exchanges and thus, tolerable environmental con di tions for tennis. Finally, these data enabled an evaluation of the current Extreme Heat Policy and the suggestion of an alternative method for assessing heat stress in tennis (the Bel di ng and Hatch Heat Stress Index).